Strengthening Vocational Technical Education Pedagogy for Knowledge Economy - E.O, Ugwoke; F.M, Onu; M.U, Agboeze (Journal of Home Economics Research, 2024)
The study determined the implications of knowledge economy on pedagogy, learning process and enhancement of VTE programmes in Nigeria. It adopted descriptive survey research design. The study was conducted in universities, in south eastern Nigeria. The population for the study consisted of 127 lecturers in vocational technical education in the Universities. A 43-item questionnaire was used for data collection. Out of 127 copies of the questionnaire administered, 118 copies were returned and analyzed using mean and standard deviation. The study found that educators should make adequate use of ICT, simulation and experiential facilities/exercises in instructional delivry while learning should be based on knowledge creation and application. It was also found from the study that collegiality and collaborative exchange between VTE institutions should be promoted for programme enhancement.